Lightnin' Hopkins : his life and blues - Govenar, Alan B., 1952- (Chicago Review Press, 2010)
Based on scores of interviews with the artist's relatives, friends, lovers, producers, accompanists, managers, and fans, this biography of Lightnin' Hopkins reveals a man of many layers and contradictions. It chronicles his life on the open road playing blues music and doing odd jobs.